2006
DOI: 10.1063/1.2402882
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal, asymmetry, and role of uncompensated spins in perpendicular exchange coupled systems

Abstract: International audienceSoft x-ray resonant magnetic scattering has been used to investigate the element-selective microscopic magnetization reversal behavior of room temperature perpendicular exchange coupled ferromagnetic/antiferromagnetic (F/AF) systems and to study the role of the interfacial coupling strength on it. Different nucleation processes and domain size distributions along the decreasing and increasing branches of the reversal have been found. The size of the magnetic domains during reversal depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed. 25,28,29,35,36 For some systems, rounded transitions in M ʈ and larger M Ќ values are found in the descending branch, 20,21,[25][26][27][28][34][35][36] where the field is applied parallel to the exchange-bias direction, while other systems display the opposite behavior. [21][22][23][24][25][29][30][31][32][33] Our results indicate that this discrepancy is related to the difference between a collinear and a noncollinear anisotropy case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed. 25,28,29,35,36 For some systems, rounded transitions in M ʈ and larger M Ќ values are found in the descending branch, 20,21,[25][26][27][28][34][35][36] where the field is applied parallel to the exchange-bias direction, while other systems display the opposite behavior. [21][22][23][24][25][29][30][31][32][33] Our results indicate that this discrepancy is related to the difference between a collinear and a noncollinear anisotropy case.…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetries in the magnetization reversal have been observed for many FM/AFM systems with both in-plane [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and perpendicular 35,36 anisotropy for the FM layer. In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has already been found that pinned (unpinned) uncompensated AFM spins at the interface are correlated with the exchange bias 18 (coercivity enhancement). 19 These features have been addressed in both in-plane and perpendicular 20 exchange coupled FM/AFM systems. However, a microscopic imaging of most of the aforementioned effects during magnetization reversal, i.e., in external magnetic fields, is still lacking.…”
Section: Fm/afm Exchange Coupling Phenomenamentioning
confidence: 99%
“…The smaller domain periodicity found for the thicker sample (n ¼ 8) has been also found in perpendicular exchange-biased [Pt/Co] n / FeMn systems by means of soft x-ray magnetic scattering measurements. 20 This originates from the low dimensionality and the minimization of dipolar effects in perpendicular anisotropy systems. The domain size is determined by the balance between the magnetostatic energy, which reduces upon domain formation, and the domain wall energy.…”
Section: Holography Imagingmentioning
confidence: 99%
“…It has been revealed that the forward and backward branches of the magnetization reversal are performed in different modes, such as the separated ways of magnetic moment rotation [5][6][7][8], the distinct nucleation sites and abilities of the inverse domain [9][10][11][12][13][14][15][16][17][18], and the unsymmetrical training and recovering effect of the pinning of the UCAS [3,[19][20][21][22]. Most AMRBs, except for the loop shift, have their particular features in the specific EB systems, which strongly depends on the structure [1,4,23,24] and measuring methods [4,[9][10][11][25][26][27][28]. The appearances of the AMRBs are so complex that the comprehension on the origin and the classification of the AMRBs is still in debate.…”
mentioning
confidence: 99%